Contribution of The Root To Slope Stability - Khalilnejad, Abdolhossein; Osman, Normaniza; Ali, F.H. (Springer Verlag, 2012)
Land sliding is a geotechnical event that includes a wide range of ground movements such as rockfalls, deep failure of slopes and shallow debris flows, and it can cause various problems in varied civil fields such as roads and dams. Since most conventional methods are neither inexpensive nor applicable everywhere, attention has nowadays been drawn to soil bioengineering using vegetation as the environment-friendly method for slope stabilization. Soil bioengineering or using vegetation in civil engineering design is mostly applicable to shallow slope stabilization projects characterized by unstable slopes with surface movement. Vegetation has both a silent effect on soil improvement to predict the landslide and a mechanical role to increase shear and pulling-out stress on the soil. During the last decade, many researches have been carried out to clarify the effect of vegetation on slope stability, but many questions still remain to be answered.